Electrocaloric temperature changes in epitaxial Ba1−xSrxTiO3 films - Magalhaes, B.; Engelhardt, S.; Molin, C.; Gebhardt, S. E.; Nielsch, Kornelius; Huehne, R. (Journal of Alloys and Compounds, 2022)
The basic aim of our study is to investigate the correlation between structural parameters and the electrocaloric effect in lead-free epitaxial Ba1−xSrxTiO3 (BSTO) based thin film architectures. Therefore, BSTO thin films with Sr contents of x = 0 to x = 0.3 were grown on SrRuO3 buffered SrTiO3 single crystalline substrates by pulsed laser deposition. Structural characterization verified an epitaxial growth for all Sr contents with an additional tetragonal distortion compared to bulk material. Temperature and frequency-dependent measurements of dielectric properties revealed increased permittivity values for thicker films with broad maxima indicating a diffuse phase transition. The temperature of maximum permittivity decreases with increasing Sr content, whereas polarization measurements indicate a relaxor-like behaviour in particular above room temperature. Adiabatic temperature changes were determined with the indirect method resulting in |ΔT| values of up to 2.9 K for a 680 nm thick BSTO layer with x = 0.3 at an applied electric field of 750 kV cm−1.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Electocaloric effect; Epitaxy; Ferroelectrics; Pulsed laser deposition; Thin films